The Role of Religious Leaders and Social Media Influencers in Promoting Participation in Online Infaq and Shadaqah in Indonesia: A Social Influence Theory–Based Analysis - Jati Imantoro; Annisa Rakhma Dewi (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: The digital era has brought profound transformations across various aspects of social life, including religious practices. This article aims to examine the role of religious leaders and social media influencers in promoting public participation in online infaq and shadaqah. Methodology: Employing a literature-based approach combined with qualitative analysis of relevant scholarly sources, this study identifies key strategies, challenges, and collaborative potentials between religious leaders and influencers in leveraging digital platforms for philanthropic purposes. The article underscores content engagement, transparency, and accessibility as key drivers of sustained participation in online donation platforms. Findings: The findings offer valuable insights for religious organizations and online donation platforms in designing effective strategies to enhance digital philanthropy in Indonesia. From a theoretical perspective, this article draws on Social Influence Theory to explain how the religious authority of clerics and the digital popularity of influencers function as agents of social influence in shaping public attitudes and donation behaviors. The main findings indicate that the internalization of digital philanthropic values occurs through a combination of normative authority, social identification, and symbolic persuasion mediated by digital platforms. This study enriches Islamic philanthropy scholarship by emphasizing social actors as key components of the digital donation ecosystem.